Long-term culture of human lung adenocarcinoma A549 cells enhances the replication of human influenza A viruses - Ujie, Michiko; Takada, Kosuke; Kiso, Maki; Sakai-Tagawa, Yuko; Ito, Mutsumi; Nakamura, Kazuya; Watanabe, Shinji; Imai, Masaki; Kawaoka, Yoshihiro (Journal of general virology, 2019)
Long-term culture of the human lung adenocarcinoma cell line A549 promotes the differentiation of these cells toward an alveolar type II cell phenotype. Here, we evaluated the susceptibility of long-term cultured A549 cells to human influenza viruses. A549 cells were cultured continuously for 25 days (D25-A549) or 1 day (D1-A549) in Ham’s F12K medium. Six human influenza A viruses grew much faster in D25-A549 cells than in D1-A549 cells; however, two influenza B viruses replicated poorly in both cell types. Two avian influenza viruses replicated efficiently in both cell types, with similar titres. Expression levels of human virus receptors were higher in D25-A549 cells than in D1-A549 cells. D25-A549 cells thus more efficiently support the replication of human influenza A viruses compared with D1-A549 cells. Our data suggest that long-term cultured A549 cells will be useful for influenza A virus research.